Improving Student Vocabulary Through Loci Method at 11th Grade Of SMK Teknologi Nasional Bekasi - Nur Hikmah; Nurhendi Nurhendi (Universitas Panca Sakti Bekasi, 2022)
Language is very important for students at school and in everyday life. Language is the ability of people to communicate with each other through signs such as words and body language. Language consists of four skills that every student needs to learn, listening, speaking, reading, and writing. The most important thing to learn from the four skills that need to be learned first is speaking. Through talking, one can relax, share thoughts and feelings, get information, learn more, and improve speaking. If students can master these four skills, it will be easier to follow how the world is changing. This journal discusses how to quickly and easily remember a language or vocabulary, because having more vocabulary can help in communicating. By learning a language, students will get more vocabulary by using this loci method. Many academics understand how important vocabulary is and how it helps people learn and teach languages. The purpose of this study is to discuss one of the research methods used by the Bekasi National Technology Vocational High School (SMK) and the factors that explain why low student achievement in study language foreign languages, specifically English. The locus method helps people remember these plans. This method is well known and considered by many to be one of the best ways to remember words in a foreign language